2022
DOI: 10.3389/fpubh.2022.830201
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to Cannabis Use and Public Prevention Information Among Young Adults: A Qualitative Interview Study With Implications for Prevention Practice

Abstract: BackgroundCannabis use carries an increased risk of ill health and social problems, especially when initiated at a young age. Drug use is influenced by individual beliefs, knowledge, and attitudes, which are, in turn, governed by social and environmental factors. In recent years, a less restrictive attitude toward cannabis has been observed in many countries, with concerns about increased cannabis use among young people. The aim of the current study was to gain a deeper understanding of young adults' attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
0
6
0
1
Order By: Relevance
“…In addition to RCTs, some qualitative studies highlighted barriers of harm reduction information, mainly in cannabis use. Young people often felt that public health information on cannabis was not credible, as it was too focused on harms [58]. Young people expressed the need for neutral information that was developed by their peers and was presented by individuals they could identify with or famous people [58,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to RCTs, some qualitative studies highlighted barriers of harm reduction information, mainly in cannabis use. Young people often felt that public health information on cannabis was not credible, as it was too focused on harms [58]. Young people expressed the need for neutral information that was developed by their peers and was presented by individuals they could identify with or famous people [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Young people often felt that public health information on cannabis was not credible, as it was too focused on harms [58]. Young people expressed the need for neutral information that was developed by their peers and was presented by individuals they could identify with or famous people [58,59]. This further supports that there is a need for research Key: ALA: alpha-lipoic acid; MSM: methylsulfonylmethane; SSRI: selective serotonin reuptake inhibitors; 5-HTTP: 5-hydroxy tryptophan 142 into how harm reduction information could be effectively delivered for people who use ecstasy or other recreational drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions of cannabis use amongst cannabis users and abstainers have varied widely but remained optimistic regarding its potential benefit and its management of possible harmful adverse effects. However, due to public information lacking in quantity and quality, the results and adverse effects of cannabis can easily be interpreted and misrepresented, calling for more attention to be placed on providing educational information for the public [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, through scrutiny of medical records, we showed that cannabis use in adolescence is associated with higher levels of hospital use, likely partly due to continued use of cannabis during follow‐up. The ongoing debate on legalization, and the apparently low risk perception of cannabis use in adolescence 33,34 indicate the need for interventions to mitigate against problematic cannabis use in young people.…”
Section: Discussionmentioning
confidence: 99%